Pulmonary hypertension: Biomarkers - Rhodes,CJ; Wharton,J; Wilkins,MR (2013)
Physicians look to biomarkers to inform the management of pulmonary hypertension (PH) at all stages, from assessing susceptibility through screening, diagnosis, and risk stratification to drug selection and monitoring. PH is a heterogeneous disorder and currently there are no accepted blood biomarkers specific to any manifestation of the condition. Brain natriuretic peptide and its N-terminal peptide have been most widely studied. Other candidate prognostic biomarkers in patients with pulmonary arterial hypertension (PAH) include growth and differentiation factor-15, red cell distribution width, uric acid, creatinine, inflammatory markers such as interleukin-6, angiopoietins, and microRNAs. Combining the measurement of biomarkers reflecting different components of the pathology with other modalities may enable better molecular characterisation of PH subtypes and permit improved targeting of therapeutic strategies and disease monitoring. © Springer-Verlag Berlin Heidelberg 2013.